ANNA LAETITIA BARBAULD AND THE DISCOURSE OF WASHlNG - Bordo, Haley (My University, 2011)
This study treats the "feminism" of Anna Laetitia Barbauld (1743-1825), a middle class English woman who is notably responsible for refashioning children's literature and for advocating the teaching of conformity in childhood education. Though her work has been relatively unexplored, Barbauld was one of the most versatile and prolific writers of her time. This thesis explores what proves to be her most pivotal text, "Washing-Day" (1797), a poem that is particularly indicative of Barbauld's "feminist" and poetic ingenuity. I begin with an introductory chapter that discusses the exclusion of Barbauld and her female Romantic counterparts from public discourse. In this discussion, I consider strategies for integrating these "new" poets into literary studies, and suggest that we must read their texts closely-which entails isolating the ambivalences and self-differences wherein the breath of the poetry subsists. I then turn to a tropological manoeuver inherent in Barbauld's poetry, which I have called "interruption," and examine how this manoeuver operates within and without "Washing-Day." In Chapter One, I theorize the "breath" of "Washing-Day"-that is, how Barbauld performs and occupies the texts of her forefathers in the process of authorizing herself to write. The second chapter circles back to the poem's beginning and analyzes Barbauld's "interruption" of patriarchal texts and discourses. Having worked through the poem in two close analyses, I arrive at the conclusion that Barbauld's feminism is performative, that it tacitly operates at the level-or movement-of difference.
Keywords: English Language and Literature; Feminist, Gender, and Sexuality Studies; English Language and Literature